PELATIHAN MACROMEDIA FLASH GUNA PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF GURU DI KOTA SEMARANG - Yunus Anis; Retnowati Retnowati; Hersatoto Listiyono; Eko Nur Wahyudi (Intimas, 2022)
This Macromedia Flash training aims to introduce macromedia flash software to teachers in the city of Semarang, especially in the environment around the Stikubank University campus, Semarang. This training focuses on how to make interactive learning media so that it is hoped that teachers can make them easily and can help the teaching and learning process in schools. As we know, since the corona-19 pandemic, the teaching and learning process is mostly done online, so with interactive learning videos it is hoped that it can help teachers teach learning materials to students. The method used in this activity is that because face-to-face learning (PTM) has begun to be applied, the process can be carried out directly to the teachers, so that the results can be directly seen and felt by the teachers. Participants can learn to make learning media using macromedia flash directly and face to face. After the participants understand the basic steps in making simple animations, then at the meeting at the end of this training each participant is taught how to make simple interactive media, and almost one hundred percent of the participants are able to make it.